2013
DOI: 10.1108/jea-05-2012-0066
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the terrain of educational leadership and management in East Asia

Abstract: Purpose -The purpose of this paper is to gain perspective on the extent to which the vision for knowledge production in East Asia set forth by Bajunid, Cheng, Hallinger, Walker, Dimmock and others almost 20 years ago has been fulfilled. The authors undertook an effort to map the terrain of knowledge production in educational leadership and management in East Asia since the year 2000. Their method of mapping this terrain involves the analysis of trends in publication of articles about and/or from East Asia in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
115
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 40 publications
17
115
1
4
Order By: Relevance
“…Findings from the review confirmed anecdotal observations made by scholars over the preceding 20 years (e.g., Bajunid, 1996;Cheng, 1995;Hallinger, 1995;Walker & Dimmock, 2002). More specifically, the research review yielded four key findings of relevance for this paper (Hallinger & Bryant, 2013b, 2013c. (1) The overall level of research output from Asia contained in these eight journals was low, representing only 4% of the total corpus published between 1995 and 2013.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…Findings from the review confirmed anecdotal observations made by scholars over the preceding 20 years (e.g., Bajunid, 1996;Cheng, 1995;Hallinger, 1995;Walker & Dimmock, 2002). More specifically, the research review yielded four key findings of relevance for this paper (Hallinger & Bryant, 2013b, 2013c. (1) The overall level of research output from Asia contained in these eight journals was low, representing only 4% of the total corpus published between 1995 and 2013.…”
supporting
confidence: 73%
“…With these same concerns in mind, we recently undertook research aimed at assessing patterns of knowledge production in educational leadership and management in Asia (Hallinger & Bryant, 2013). We reviewed the Asian literature published in eight of the key international, refereed educational leadership and management journals between 1995 and 2012 (Hallinger & Bryant, 2013b, 2013c. Findings from the review confirmed anecdotal observations made by scholars over the preceding 20 years (e.g., Bajunid, 1996;Cheng, 1995;Hallinger, 1995;Walker & Dimmock, 2002).…”
supporting
confidence: 62%
See 3 more Smart Citations